Photograph-based seed cone counts of white spruce (Picea glauca) trees from treeline field sites across the Brooks Range, Alaska 2019-2022 ... - Maher, Colin; Sullivan, Patrick; Dial, Roman; Hewitt, Rebecca (NSF Arctic Data Center, 2023)
Photograph-derived counts of seed cones on white spruce (Picea glauca) trees at elevational (alpine) & lower (arctic) treelines at 19 research sites along a west-east gradient in Alaska's Brooks Range. Photographs are from a single angle and thus represent a "cone production index" rather than a complete count of all the cones on a tree. The general purpose of the sampling was to examine west-east variation in white spruce growth responses to changes in climate. ...